Experimental investigation on the rheological behaviour and dynamic viscosity of coconut oil based Al2O3-TiO2hybrid nanofluid - Purushothaman H.; Wanatasanappan V.V. (American Institute of Physics Inc., 2024)
This study focuses on the experimental investigation of the rheological behaviour and dynamic viscosity of coconut oil based Al2O3-TiO2 hybrid nanofluid for transformer cooling with mixing ratios of 25:75,:50:50 and 75:25. The purpose of the study is to investigate the effect of nanoparticle mass concentration, nanofluid temperature and shear rates on the viscosity behaviour of the nanofluid developed. Besides, the rheological behaviour of the nanofluid also studied experimentally. The temperature and concentration studied spans from 30C to 70C and 0 - 0.5% respectively at a shear rate of 50s-1. An Anton Pars MCR 92 rheometer was used to measure the dynamic viscosity of the nanofluid. The experimental results indicated that with the increase in temperature from 30C to 70C and concentration from 0 to 0.5%, the dynamic viscosity increase by approximately 32%. Based on the results obtained, this nanofluid is justified to behaves as a Newtonian fluid at a higher shear rate, and a mixing ratio of 50:50 with a concentration of 0.5 wt% are most suitable due to stable trends. 2023 Author(s).